Development and initial clinical correlation of a DNA methylation‐based blood test for prostate cancer. Issue 12 (7th June 2020) - Carson, Jacob J. K.; Di Lena, Michael A.; Berman, David M.; Siemens, D. Robert; Mueller, Christopher R.
Abstract: Background: One of the principle limitations for more precise management of advanced prostate cancer is the lack of accurate biomarkers allowing estimation of tumor burden, ongoing assessment of progression, and response to treatment. Although prostate‐specific antigen (PSA) performs modestly, nonsecreting cancers including those with early castrate‐resistance warrant investigation of other predictive biomarkers. The objectives of these studies were to develop and perform initial validation of a circulating tumor DNA (ctDNA) methylation assay. Methods: Methylation DETection of Circulating Tumor DNA (mDETECT) is a highly multiplexed targeted sequencing DNA methylation‐based ctDNA blood test that captures the vast majority of prostate cancer phenotypes due to a careful development process that ensures that each probe region is methylated in at least 50% of all methylation‐based subtypes and is not methylated in normal tissues. Next‐generation sequencing of targeted polymerase chain reaction (PCR) products whose amplification is biased towards methylated DNA ensures the specificity of the assay by identifying multiple tumor‐specific methylated CpG residues in each read. Results: The final test is comprised of 46 PCR probes to 40 regions. It is relatively resistant to contaminating normal DNA and as a result functions in both serum and plasma samples. The assay was initially validated in a variety of prostate cancer cell lines to ensure specificity. Using a small number of longitudinal samples from prostate cancer patients initiating androgen deprivation therapy, the ability of mDETECT to track tumor burden was assessed compared with PSA. The mDETECT test signal generally paralleled that of PSA increasing and decreasing commensurate with tumor evolution in these patients. In two cases it appeared to anticipate clinical progression by a number of months compared to PSA and in a PSA nonproducing case, it was able to track tumor progression. Conclusions: mDETECT offers a promising tool for the assessment of prostate cancer burden based on the sensitive detection of prostate‐specific ctDNA and requires further validation.